Perlindungan Hukum Terhadap Perempuan Sebagai Korban Kekerasan dalam Rumah Tangga - Pramitasari, Anisya Rizky (CV WAHANA PUBLIKASI, 2023)
In Indonesia, cases offrviolence against women are quite high, where violence against womenbtoften occurs in the domestic sphere (household environment) or what is often called domestic violence (KDRT). Domestic violence is divided into two types, namely physical and non-physical, physical violence is an action that physically injures the victim, while non-physical is an action that harms the victim from a psychlogical perspective which results in psychological disorders of the victim. Legalzwprotection for women aswsvictims of domestic violence is still relatively low due to the lack ofvrfollow-up on cases and obstacles from the community itself. The aim of this research is to determine thezwlegal protection efforts provided to women as victims of domestic violence. This research waswzconducted based on normative juridical research, using an approach of reviewing legislation and literature in accordance with the problem being studied.